Metal artifact reduction in photon-counting detector CT: quantitative evaluation of artifact reduction techniques - Skornitzke, Stephan; Mergen, Victor; Biederer, Jürgen; Alkadhi, Hatem; Do, Thuy; Stiller, Wolfram; Frauenfelder, Thomas; Kauczor, Hans-Ulrich; Euler, André (Investigative radiology, 2024)
Objectives - With the introduction of clinical photon-counting detector computed tomography (PCD-CT) and its novel reconstruction techniques, a quantitative investigation of different acquisition and reconstruction settings is necessary to optimize clinical acquisition protocols for metal artifact reduction. - Materials and Methods - A multienergy phantom was scanned on a clinical dual-source PCD-CT (NAEOTOM Alpha; Siemens Healthcare GmbH) with 4 different central inserts: water-equivalent plastic, aluminum, steel, and titanium. Acquisitions were performed at 120 kVp and 140 kVp (CTDIvol 10 mGy) and reconstructed as virtual monoenergetic images (VMIs; 110-150 keV), as T3D, and with the standard reconstruction “none” (70 keV VMI) using different reconstruction kernels (Br36, Br56) and with as well as without iterative metal artifact reduction (iMAR). Metal artifacts were quantified, calculating relative percentages of metal artifacts. Mean CT numbers of an adjacent water-equivalent insert and different tissue-equivalent inserts were evaluated, and eccentricity of metal rods was measured. Repeated-measures analysis of variance was performed for statistical analysis. - Results - Metal artifacts were most prevalent for the steel insert (12.6% average artifacts), followed by titanium (4.2%) and aluminum (1.0%). The strongest metal artifact reduction was noted for iMAR (with iMAR: 1.4%, without iMAR: 10.5%; P < 0.001) or VMI (VMI: 110 keV 2.6% to 150 keV 3.3%, T3D: 11.0%, and none: 16.0%; P < 0.001) individually, with best results when combining iMAR and VMI at 110 keV (1.2%). Changing acquisition tube potential (120 kV: 6.6%, 140 kV: 5.2%; P = 0.33) or reconstruction kernel (Br36: 5.5%, Br56: 6.4%; P = 0.17) was less effective. Mean CT numbers and standard deviations were significantly affected by iMAR (with iMAR: −3.0 ± 21.5 HU, without iMAR: −8.5 ± 24.3 HU; P < 0.001), VMI (VMI: 110 keV −3.6 ± 21.6 HU to 150 keV −1.4 ± 21.2 HU, T3D: −11.7 ± 23.8 HU, and none: −16.9 ± 29.8 HU; P < 0.001), tube potential (120 kV: −4.7 ± 22.8 HU, 140 kV: −6.8 ± 23.0 HU; P = 0.03), and reconstruction kernel (Br36: −5.5 ± 14.2 HU, Br56: −6.8 ± 23.0 HU; P < 0.001). Both iMAR and VMI improved quantitative CT number accuracy and metal rod eccentricity for the steel rod, but iMAR was of limited effectiveness for the aluminum rod. - Conclusions - For metal artifact reduction in PCD-CT, a combination of iMAR and VMI at 110 keV demonstrated the strongest artifact reduction of the evaluated options, whereas the impact of reconstruction kernel and tube potential was limited.